Factors associated with the uptake of cataract surgery among adults identified with operable cataract in South Western Uganda - Kanji R; Onyango J; Twinamasiko A; Arunga S (Journal of Ophthalmology of Eastern, Central and Southern Africa (JOECSA), 2025)
Objective: To determine the factors associated with the uptake of cataract surgery among adults identified with operable cataract in South Western Uganda. Methods: In a hospital-based cross-sectional study, patients presenting with operable cataract at two large tertiary level eye hospitals in south-western Uganda were prospectively consecutively enrolled between, October 2020 to January 2021. Operable cataract was defined, as a best-corrected visual acuity equal or less than 6/60 where the principal cause is cataract. The outcome of interest was undergoing a cataract surgery within 3 months of diagnosis. In a multivariable logistic regression model, we tested for social demographic and other baseline features associated with uptake of a cataract operation. Results: During the study period, a total of 400 patients with operable cataract were enrolled out of a total outpatient attendance of 1692 in the two hospitals (23.6%). The median age was 71 (IQR 65-80, full-range 30-102) and 222 (55.5%) were female. Most were married 242 (60.5%), the majority with no formal education 184 (46%). The most common occupation was being a peasant 256 (64%). The majority of the patients were household heads 285 (71.2%) and a large proportion required an escort to the hospital 384 (87%). Bilateral operable cataract was present in 146 (36.5%). Within the study period, the uptake of cataract surgery was 64% 95% CI (59- 68). In a multivariable logistic regression model, <50 years (OR 3.0, 95% CI (1.26 – 7.23) P-value = 0.021), female gender (OR 1.5, 95% CI (1.04 – 2.34) P-value=0.032) and bilaterally affected eyes (OR 2.95, 95% CI (1.8 – 4.8) P-value 0.001) were associated with uptake of cataract surgery. Conclusion: This study showed that younger patients compared to older ones, females compared to males and bilaterally affected patients compared to unilateral were more likely to uptake cataract surgery. This provides useful background information for planning improvements in the uptake of cataract services.
Keywords: Cataract; Factors associated; Uptake; Gender; Age; Bilateral cataract; Hospital-based